ANALISIS PENGARUH KINERJA KEUANGAN, GOOD CORPORATE GOVERNANCE, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN (Studi empiris pada perusahaan yang terdaftar dalam LQ-45 tahun 2014-2016) - Lufi Khomsiatin Nulhaniya; Ronny Malavia Mardani; Agus Salim (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT The purpose of thisstudywastodetermineandanalyzefinancial performance, goodcorporategovernance, andcorporatesocialresponsibilitytowardsthefirmvalue of empiricalstudies on companieslistedin LQ-45 on the 2014-2016 sampling techniqueusingpurposive sampling is a consideration of certaincriteria. . The data analysistoolusedinthisstudyistheMultiple Linear RegressionAnalysis.Based on theresults of thisstudy, itisknownthatthevalue of t arithmetic on the ROE -100 variableshowstheSigvalue of 0.920 smallerthan 0.05 andthe t valueiscalculated on the CSR variable of -0.532 with a Sig 0.597 sothatitcanbeconcludedthat ROE and CSR have a significantpositiveeffect on thevalue of thecompany. Whilethe GCG variable has a value of 0.316 twith a value of 0.753 sigdoes not have a significantpositiveeffect on companyvalue. Keyword : ROE, GCG, CSR andthevalue of thecompany